2011
DOI: 10.1116/1.3607410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and near-substrate plasma density on the structural and electrical properties of dc sputtered germanium thin films

Abstract: Germanium thin films were deposited by dc reactive magnetron sputtering as a function of substrate temperature and ion flux using an unbalanced magnetron with an external magnetic field. The ion flux and energy distribution were measured using a retarding field energy analyzer (RFEA), a flat probe with a guard ring, and cylindrical Langmuir probes. The RFEA ion flux, the flat probe saturation currents, and the ion densities inferred from the cylindrical probe data are in very good agreement over a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6]. This technique is one of the most popular in science and technology due to the high quality of the deposited films, the possibility to work on large substrates as well as to the high deposition rates achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. This technique is one of the most popular in science and technology due to the high quality of the deposited films, the possibility to work on large substrates as well as to the high deposition rates achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The sputtering of the ultra‐thin Si layer on the Si wafer is for the purpose of presenting a surface conducive for the subsequent growth of Ge. Prior studies on Ge sputter deposition have indicated that the underlying surface can create a difference in the nucleation dynamics of Ge [5]. The ultra‐thin Si layer can function as a nucleation layer for the subsequent Ge deposition.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of the ultra‐thin Si intermediate layer, the spectrum does not show any peaks pertaining to polycrystalline Ge. A rather broad diffraction peak is barely discernible around 2 θ of 25°, which can be attributed to a fully amorphous structure [5]. In the case of Ge film deposited on Si wafer at the same process temperature with an ultra‐thin intermediate Si layer, diffraction peaks are clearly visible at 2 θ values around 27.3° and 45.3° and 53.7°.…”
Section: Resultsmentioning
confidence: 99%